The qur'an and the formation of the intellectual (scientific) mind - Hashi, Abdurezak Abdulahi (2010)
In the process of building knowledge-based civilization, scientific progress and technological advancement is both important and challenging task. However, equally important and challenging task is "forming" the scientific mind and "shaping" the intellectual behaviour of individuals to develop science and technology. While such claim seems to be apparently noticeable fact, among various questions raised are; if the formation of the scientific mind is a pre-requisite for the progress of science, what are the necessary steps of forming the scientific mind? How to improve the human ability of knowledge production? What are the educational stepladders to improve the competence of human intellectual mind? This paper attempts to answer, at least, some of these questions through and within the Qur'anic perspective. This is because, though the Qur'an is not a scientific book which contains historical and laboratory details of science and technology, however, as a book of guidance it incorporates vital descriptions related to knowledge and methods of improving human ability of acquiring knowledge. Through analytical and textual methods, this paper aims to expose the rudimentary elements of the Qur'anic perspective of improving scientific mind and intellectual behaviour of man, including; reading continuously with understanding, the culture of learning, authentication of received information, objectivity with the subject of knowledge, and to avoid depending on doubts and superstitions in the learning process. While the Qur'anic terms and the Prophetic statements related to the subject would be exposed, the opinions of the Muslim exegetes of the Qur'an and theologians related to the subject would be unveiled.